CHEMICAL COMPOSITION AND IN VITRO ANTILITHIATIC POTENTIAL OF BIOFLAVONOIDS FRACTIONATED FROM PHYLLANTHUS NIRURI SEED - Varpe S. N,; Khedkar S.A., Kadlag S.D.,; Gagare Y.S., Satralkar A.S., (EPRA International Journal of Multidisciplinary Research (IJMR), 2022)
Kidney stone (Lithiasis) is the formation of calculi or urinary stone which is a concretion of material mainly mineral salts in any part of the body. One of the major causes of acute and chronic renal failure is lithiasis (Stone formation) which includes both nephrolithiasis (stone formation in the kidney) and urolithiasis (stone formation in the ureter or bladder or both). Of many types of stones that are formed, the most common are calcium oxalate. The formation of such concretion encompasses several physicochemical events beginning with crystal nucleation, growth, aggregation, and ending by retention within urinary tract. The present study is to reveal the in vitro antilithiatic activity of Phyllanthus niruri (Fam: Phyllanthaceae) seeds and its chemical characterization. Phyllanthus niruri (Fam: Phyllanthaceae) is a widespread tropical plant commonly known as stone breaker. It is a plant used for the treatment of kidney stone by tribal people. The seeds of this plant are suggested for the patients of the kidney stone. From this project it can be concluded that the phenolic compounds isolated from seed extract is able to inhibit CaC2O4 crystallization in vitro and thus it can be confirmed to have antilithiatic property.